ANALISIS BEBAN KERJA PADA UNIT REKAM MEDIS DI RUMAH SAKIT DR. HAFIDZ CIANJUR - Ismatul Faujiah (Jurnal Infokes, 2023)
The implementation of quality medical records requires quality health workers and in accordance with their competence. A good workforce has a significant influence on the quality of service in the medical record work unit. To achieve quality service, it is important to ensure that the number of workers available is in accordance with the needs so that the service becomes quality. The quality of service in the medical record work unit is greatly influenced by a competent workforce. The quality of this service is related to the workload, so it is important to maintain a balance between workload and the number of staff so that the service becomes quality. Workload refers to the number of tasks and responsibilities given to the workforce, both physically and mentally. Each job is considered a burden for the individual who performs it, and each workforce has a different ability to handle their own workload. Workload can be in the form of physical, mental, or social demands that must be overcome by the workforce. Workload has a significant impact on the efficiency, effectiveness and productivity of the workforce. Therefore, it is important to strike a balance between the amount of manpower available and the workload to be handled within a given service unit. One of the methods used to determine workforce needs is the ABK-Kes (Health Workload Analysis) method, which can indicate the number of workers needed in health facilities based on workload. This method helps simplify the process of placing or readjusting the workforce in an easier and rational way. Thus, meeting the right workforce needs will contribute to creating quality services in the Medical Record work unit.Keywords: Workload, Medical records, Service Quality